Cooperation benefits of Caspian countries in their energy sector development - De Miglio, Rocco; Akhmetbekov, Yerbol; Baigarin, Kanat; Bakdolotov, Aidyn; Tosato, GianCarlo (My University, 2014)
Abstract This paper studies the development possibilities of the energy systems of four Central Asia and Caspian countries. It explores options that improve their domestic energy efficiencies and increase their export of fossil energy commodities. Using the MARKAL-TIMES modelling tool, it represents their energy system with a bottom-up partial economic equilibrium growth model. With the help of scenario analyses, it evaluates the direct economic advantage of improving the domestic energy efficiencies. Furthermore it calculates the direct economic advantage of cooperation. It finds out that a new/different geo-economic attitude brings USD billions of annual economic benefits, particularly if the countries aim to differentiate their export routes, increase the amount of export and contribute to climate change mitigation.
Keywords: Caspian oil and gas; Export-oriented scenarios; Cross-country infrastructures; Energy systems analysis; Technical economic growth models; Energy balances and statistics